2015
DOI: 10.1111/jace.13921
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Property of (Nb2O5, SrCO3, Ge, GeO2)‐Codoped TiO2‐Based Varistor Ceramics

Abstract: This study investigated the influence of codoping with Ge and GeO2 on the nonlinear coefficient α and the breakdown voltage EB of TiO2–Nb2O5–SrCO3 varistor ceramics. Ge–GeO2 codoping notably changed the microstructure of the TiO2–Nb2O5–SrCO3 ceramics, increased α, and decreased EB. When the doping contents of Nb2O5 and SrCO3 were 0.1 and 0.2 mol%, respectively, the optimum doping content of 0.25 mol% Ge and 0.75 mol% GeO2 exhibited high α (11.6), low EB (13.8 V/mm), and high grain‐boundary barrier ΦB (0.96 eV)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Parameters such as ¡, E B , and leakage current (J L ) were measured using a varistor direct-current instrument. The grain boundary barrier height () B ) of the samples was calculated using the following formula: 19…”
Section: Methodsmentioning
confidence: 99%
“…Parameters such as ¡, E B , and leakage current (J L ) were measured using a varistor direct-current instrument. The grain boundary barrier height () B ) of the samples was calculated using the following formula: 19…”
Section: Methodsmentioning
confidence: 99%
“…Wang et al synthesized Ge@ graphene@TiO 2 nanofibers as high‐capacity and cycle‐stable anode for lithium and sodium ion battery. Kang et al investigated the nonlinear properties of Ge and GeO 2 co‐doped TiO 2 . Long et al found Ge‐doped TiO 2 can be active for overall water splitting.…”
Section: Introductionmentioning
confidence: 99%